2020
DOI: 10.1002/ece3.6916
|View full text |Cite
|
Sign up to set email alerts
|

Course‐based undergraduate research experiences in a remote setting: Two case studies documenting implementation and student perceptions

Abstract: Similar to many institutions, Reed College (Portland, OR) transitioned to a remote leaning environment in Spring 2020, with 5 weeks remaining in the semester. Historically, many of Reed's upper division courses in math and natural sciences-including Ecology (Biology 301) and an interdisciplinary Environmental Science (ES 300) Junior Seminar (both full credit, one semester courses)-culminate in students pursuing independent research projects (IPs), a type of course-based undergraduate research experience, CURE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…Other key challenges encountered include travel restrictions, less-developed online assessments and evaluations, a lack of technical and technological skills, and a lack of online confidentiality. 2 , 9 , 24 …”
Section: Resultsmentioning
confidence: 99%
“…Other key challenges encountered include travel restrictions, less-developed online assessments and evaluations, a lack of technical and technological skills, and a lack of online confidentiality. 2 , 9 , 24 …”
Section: Resultsmentioning
confidence: 99%
“…Research experiences within courses have been shown to produce positive benefits in multiple measures of student success, including student retention in STEM fields (e.g., Corwin et al, 2018; Cooper et al, 2019; Oufiero, 2019), and our project has the additional benefit of incorporating field work. Recently, Fey et al (2020) report on other examples of CUREs that incorporate field research and were implemented under COVID‐19 restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Fey et al [3] documentaram os primeiros problemas identificados com a experiência do ensino remoto, e destacaram entre os aspectos negativos, a falta de acesso aos laboratórios -limitando as práticas de ensino ao uso de softwares; as condições de habitabilidade dos estudantes -nem sempre compatíveis com a demanda de concentração das aulas remotas; as dificuldades no acesso à Internet; e as responsabilidades adicionais dos estudantes, que entram em conflito com o tempo a ser dedicado às atividades acadêmicas, por estarem estudando de casa. As relações sociais também mudaram radicalmente como consequência da adoção das plataformas digitais.…”
Section: Contextounclassified